Exploring the Effects of Physical Activity Levels and Sleep Quality on Cognitive Failure in Elderly: A Cross-Sectional Study - Hatami, Farzaneh; Abolghasemi Atani, Shafagh; Caron, Valerie; Yousefi, Saheb (International Journal of Sport Studies for Health, 2025)
AbstractObjectives: Aging is a natural stage of life characterized by physiological and cognitive changes that increase the risk of cognitive failure. Among modifiable lifestyle factors, physical activity and sleep quality play a crucial role in maintaining cognitive function in older adults. Therefore, the present study aimed to examine the effects of physical activity levels and sleep quality on cognitive failure in Iranian older adults.Methods & Materials: To achieve the objectives of the study, a descriptive, cross-sectional study was conducted using a multistage cluster random sampling method. The study population consisted of adults aged 60 and older from five geographical regions of Iran. The data were collected using the Cognitive Failures Questionnaire (CFQ), Pittsburgh Sleep Quality Index (PSQI), and the CHAMPS Physical Activity Questionnaire for Older Adults. Finally, the data were analyzed using a two-way multivariate analysis of variance (MANOVA).Results: The results of the two-way multivariate analysis of variance (MANOVA) revealed significant main effects for both physical activity level and sleep quality, as well as a significant interaction effect between physical activity level and sleep quality on the subscales of cognitive failure (p